Effects of renal tubular dysfunction on bone in tenofovir-exposed HIV-positive patients. (10th September 2015) - Hamzah, Lisa; Samarawickrama, Amanda; Campbell, Lucy; Pope, Matthew; Burling, Keith; Walker-Bone, Karen; Gilleece, Yvonne; Fisher, Martin; Post, Frank A.
Abstract : Objectives: Tenofovir disoproxil fumarate (TDF) may cause renal tubular dysfunction (RTD) and reduce bone mineral density (BMD). We examined the relationship between RTD and BMD in TDF-exposed HIV-positive men. Design and methods: We analysed urinary retinol-binding protein/creatinine ratio (RBPCR) and fractional excretion of phosphate (FEPO4 ) to quantify RTD in a cross-sectional sample of randomly selected HIV-positive men at a single tertiary outpatient clinic. BMD at the lumbar spine and hip was measured by dual-energy X-ray absorptiometry. Multivariate logistic regression was used to analyse factors associated with RTD, and linear regression to examine the relationship between RTD and BMD. Results: Of 293 men (mean age 48 years, 94% White ethnicity, median TDF exposure 2.1 years), 22.5% had RBPCR-defined RTD and 12.3% had FEPO4 -defined RTD. We observed a negative correlation between RBPCR and BMD at the spine (β −0.2, P = 0.002) and hip (total: β −0.1, P = 0.02; femoral neck: β −0.1, P = 0.02), but not between FePO4 and BMD. In multivariable analyses, RTD defined by more than five-fold elevations in RBPCR was associated with significantly lower BMD of the spine. Conclusion: In HIV-positive patients receiving TDF-containing antiretroviral therapy, RTD was associated with lower BMD of the spine in HIV-positive men. RBPCR quantification may identify patients at increased risk of TDF-associated BMD loss.